KOMPOSISI MUSIK "PIK-PIK-NUMPANG-TIDUK": INTERPRETASI DARI SEBUAH KESENIAN TRADISI LISAN DI DESA PULAU TEMIANG, KABUPATEN TEBO, PROVINSI JAMBI - Hadaci Sidik (Puitika, 2018)
Indonesia has a very diverse diversity of traditions, so it becomes a potential asset to be explored and developed. One of the potentials of this nation can be used as a source of inspiration or ideas in creating musical compositions. Each region in Indonesia has its own traditions, such as one of the oral traditions of the people of Pulau Temian, Kabupateb Tebo, provinsi Jambi. In this area there is a story called "Pik-Pik-Numpang-Tiduk", which is a lesson about modesty that is found in a meeting between men and women. "Pik-Pik-Numpang-Tiduk" revolves around the procedures for male lovers visiting the woman's house and how customary values and kindness are maintained. This activity is the basic foundation for creating a rhythm of a motive of the star, which is called the motive of a picnic star overlapping. This motif was then developed in accordance with the contents of the story "Pik-Pik-Numpang-Tiduk". and worked on a composition of orchestral music. The creation of this musical composition through the stages of identification of musical elements, exploration of musical ideas, and experimentation on intervals found in the habits of local villagers, so that it becomes a new color in the form of orchestral music compositions that have the characteristic of one archipelago and represents a description of the story of Pik-Pik Numpang Tiduk from the village of Pulau Temiang.Keywords: Pik-Pik’ Numpang Tiduk, Kelintang